Cross-country co-movement in long-term interest rates: A DSGE approach - Michael Chin; Thomai Filippeli; Konstantinos Theodoridis (Queen Mary University of London, School of Economics and Finance, 2015)
Long-term interest rates in a number of small-open inflation targeting economies co-move more strongly with US long-term rates than with short-term rates in those economies. We augment a standard small open-economy model with imperfectly substitutable government bonds and time-varying term premia that captures this phenomenon. The estimated model fits a range of US and UK data remarkably well, and produces term premium estimates that are comparable to estimates from the affine term structure model literature. We find that the strong co-movement between US and UK long-term interest rates arises primarily via correlated policy rate expectations, rather than through correlated term premia. This is due to policymakers in both economies responding to foreign productivity and discount factor shocks that cause persistent changes in inflation. We also overcome the common failure of similar models to account for the large influence of foreign disturbances on domestic economies found empirically, where in our model around 40% of the variation in UK GDP can be explained by shocks originating in the US economy.
Keywords: E43; E44; F30; F44; F65; G15; 330; DSGE model; Small open economy; Yield curve; Long-term interest rates; Term premia; Co-movement